2014
DOI: 10.6063/motricidade.10(4).3395
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças na ativação muscular entre a realização de flexões com apoio fixo e com um sistema de suspensão unilateral em forma de V em diferentes alturas

Abstract: This study was designed to analyze upper extremity and core muscle activation performing push-ups under different stability conditions and body positions. Trained university male students (n= 29) performed 3 push-ups each under stable conditions and using suspension device (AirFit Trainer ProTM) with their hands at 2 different heights (i.e., 10 and 65 cm). Push-up speed was controlled using a metronome and the testing order was randomized. The average amplitudes of the electromyographic root mean square of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
2
14
0
2
Order By: Relevance
“…Eight studies included both male and female participants ( 51 , 53 , 58 , 61 , 69 , 71 , 73 , 74 ), while one study did not report the gender of the participants ( 72 ). Eight studies included athletes as participants ( 21 , 52 , 55 , 61 , 63 , 67 , 70 , 73 ), six studies undertook physically active individuals ( 51 , 54 , 58 , 62 , 71 , 75 ), five studies involved students ( 4 , 56 , 57 , 66 , 68 ), four studies included physically fit individuals ( 59 , 60 , 64 , 65 ), one study included both athletes and non-athletes ( 1 ), one study included both athletes and physically fit students ( 74 ), and one study included conditioning coaches and personal trainers ( 69 ). In two studies, the type of participants was not reported ( 53 , 72 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies included both male and female participants ( 51 , 53 , 58 , 61 , 69 , 71 , 73 , 74 ), while one study did not report the gender of the participants ( 72 ). Eight studies included athletes as participants ( 21 , 52 , 55 , 61 , 63 , 67 , 70 , 73 ), six studies undertook physically active individuals ( 51 , 54 , 58 , 62 , 71 , 75 ), five studies involved students ( 4 , 56 , 57 , 66 , 68 ), four studies included physically fit individuals ( 59 , 60 , 64 , 65 ), one study included both athletes and non-athletes ( 1 ), one study included both athletes and physically fit students ( 74 ), and one study included conditioning coaches and personal trainers ( 69 ). In two studies, the type of participants was not reported ( 53 , 72 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the normalization methods for EMG signals, maximum voluntary isometric contraction (MVIC) was used in 15 studies ( 4 , 51 , 52 , 56 61 , 63 65 , 68 , 73 , 75 ), maximal voluntary contraction (MVC) in eight studies ( 21 , 55 , 62 , 66 , 67 , 70 , 71 , 74 ), reference voluntary isometric contraction (RVIC) in one study ( 54 ), reference voluntary contraction (RVC) in one study ( 72 ), and reference isometric contraction (RIC) in one study ( 53 ). One study did not report the normalization method used ( 69 ), and in one study, the signals were not normalized ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the popularity of ST, several studies were performed in the last 5 years to investigate the cardiovascular [8,9], neuromuscular [10][11][12][13][14] and biomechanical [3,7,15] characteristics of this activity. The unstable nature of the base of support characterizing ST has been reported to stress the neuromuscular system with greater muscular demands than traditional resistance exercises performed on stable surfaces [13,14,[16][17][18] with subsequent increases in strength, attributable to changes in muscle cross-sectional area and neuromuscular coordination [13,19]. Therefore, acute [8,20] and chronic [21][22][23][24] improvements in strength, endurance, flexibility, functional and core stability have been reported in relation to ST, with the majority of studies focusing solely on either male or female participants and not addressing the gender-related differences.…”
Section: Introductionmentioning
confidence: 99%
“…The research results by Akhtaruzzaman et al (2016) showed that the lower limb in the leg supports superior parts: neck, head, and torso. Furthermore, Calatayud et al (2014) stated that arm muscle strength contributes to the dominant upper extremity motion pattern. Therefore, it is necessary to research the dominant factors of physical ability of athletes that support technical achievements in general artistic gymnastics and vault tools specifically.…”
Section: Introductionmentioning
confidence: 99%